A mixed-methods exploration of the quality of life of Chinese breast cancer survivors. Issue 3 (3rd May 2016) - Cheng, Huilin; Sit, Janet W. H.; Cheng, Karis K. F.
ABSTRACT: Quality of life (QOL) in cancer survivorship is a multidimensional and subjective concept, which represents the personal sense of the physical, psychological, social, and spiritual consequences of cancer diagnosis and its treatment. This mixed method study aimed to explore the QOL of Chinese breast cancer survivors. Participants were recruited from a cancer self-help organization in the central area of China. QOL was assessed using the QOL–Cancer Survivor Scale and subsequently elicited by in-depth interviews. Results showed that participants had good overall QOL but with unfavorable aspects in psychological and social well-being. Interview data revealed that participants seldom attended spiritual activities. Instead, they actively reconnected with their "self" to create a positive meaning from their cancer experience. Understanding how Chinese breast cancer survivors perceive QOL is important for health professionals to address survivorship in this population.